STELLA GRANT AND WILL NEWMAN’S CHARACTER DEVELOPMENT THROUGHOUT A MOVIE ENTITLED FIVE FEET APART - Habriani, Nana Murti; Widiadnya Putri, I Gusti Ayu Vina; Winarta, IB Gde Nova (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
This study focused on analyzing how the main characters from Five Feet Apart movie developed their character as the story progressed by using the theory of character proposed by Kenney (1966). The aim of this research was to identify how the main characters develop their character through their actions and dialogues by applying the qualitative method through several steps, such as selecting a movie and collecting data, watching the movie thoroughly, and the last step was note-taking and determining the type of the main character found in the movie by using character theory, specifically the type of character by Kenney (1966). The presentation of the analysis was supported by providing conversations from the movie to make the description clearer and coherent. It was found in this study that the main characters experienced a change from flat/simple characters to round/complex characters as the story progressed which can obviously be seen from the characters’ actions and dialogues.